Serum total bilirubin levels are negatively correlated with metabolic syndrome in aged Chinese women: a community-based study - Zhong,P. (2017)
We evaluated serum total bilirubin levels as a predictor for metabolic syndrome (MetS) and investigated the relationship between serum total bilirubin levels and MetS prevalence. This cross-sectional study included 1728 participants over 65 years of age from Eastern China. Anthropometric data, lifestyle information, and previous medical history were collected. We then measured serum levels of fasting blood-glucose, total cholesterol, triglycerides, and total bilirubin, as well as alanine aminotransferase activity. The prevalence of MetS and each of its individual component were calculated per quartile of total bilirubin level. Logistic regression was used to assess the correlation between serum total bilirubin levels and MetS. Total bilirubin level in the women who did not have MetS was significantly higher than in those who had MetS (P<0.001). Serum total bilirubin quartiles were linearly and negatively correlated with MetS prevalence and hypertriglyceridemia (HTG) in females (P<0.005). Logistic regression showed that serum total bilirubin was an independent predictor of MetS for females (OR: 0.910, 95%CI: 0.863–0.960; P=0.001). The present study suggests that physiological levels of serum total bilirubin might be an independent risk factor for aged Chinese women, and the prevalence of MetS and HTG are negatively correlated to serum total bilirubin levels.